Perceived Risk And Self Efficacy Effect On Digital Gold Applications Usage - Taufan Adi Kurniawan; Anita Primastiwi; Devy Putri Milanda (Jurnal Manajemen, 2024)
Gold prices in the last quarter of 2022 to March 2023 have increased significantly. This was caused by several reasons, such as war and two large banks' bankruptcies, namely Silicon Valley Bank and Signature Bank; many investors have switched to gold investment. Indonesians are used to gold investment; various Fintech applications have provided digital gold investment, and the government also has regulations for digital gold investments, but Indonesians still hesitate to use digital gold for investment. This study aims to analyse the effect of some factors on digital gold applications using the Technology Acceptance Model (TAM) and adding external variables such as perceived risk and self-efficacy. The results showed that all TAM variables had a positive effect, and self-efficacy and perceived risk variables also had a positive effect. This means digital gold application users in Indonesia are still affected by perceived ease of use, perceived usefulness, perceived risk of applications and self-efficacy in using digital gold applications.